Laboratory Investigation on the Effect of Fly Ash on the Compressibility of Soil - Amiralian, S; Chegenizadeh, A; Nikraz, Hamid (Planetary Scientific Research Center, 2012)
One of the key steps in geotechnical construction is study on characteristics of soil for evaluation the deficiency factors of soil properties that lead to some problems such as settlement and heave. Soil stabilization with fly ash as by-product is one of the effective methods that were applied for modifying soil properties. This paper presents a series of laboratory tests for investigation on the adequacy of fly ash on the compressibility and swelling characteristic of soil. In this research the compression index, swelling index, and initial void ratio of one un-stabilized sample and eight stabilized specimens with difference fly ash additives were investigated. Overall, the data reveal that fly ash stabilization couldreduce the consolidation property, swelling behaviour. In addition, increment in the amount of fly ash led to reduction in the initial void ratio of stabilized samples.